Lexicons in Gambuh Dance Drama - Gusti Made, Jyotika; I Gede Budasi; Dewa Ayu Eka Agustini (Universitas Pendidikan Ganesha, 2022)
Gambuh Dance-Drama is one of the most classic and old Balinese dances which is employed as a lakon, as stated in the on different sorts of functions in Balinese dance. It is a sort of whole theatrical production which combines dance and drama. Culturally, there are some lexicons that can be found in GDD especially the lexicons in movement. This study aimed to analyze the lexicons which exist in Balinese dance, especially GDD, in order to be one of strategies to avoid the extinction of Balinese language. Moreover, this study also carried out the cultural meanings which exist in lexicons of Gambuh Dance Drama related to its movements. This study was designed in the form of descriptive qualitative study using an ecolinguistic approach. Furthermore, this study focused on lexicons related to the movements which exist in GDD at Sanggar Tari Kertha Jaya in Denpasar. The obtained data were collected from observing and interviewing techniques. The steps of data analysis were divided into three categories: data reduction, data display, and conclusion, drawing, and verifying. The result of this study showed that there were thirty-two (32) lexicons in GDD and classified into: stages (4 lexicons), hand movements (9 lexicons), leg movements (4 lexicons), body movements (12 lexicons), neck movements (1 lexicon), eyes movements (2 lexicons). The dancer in Sanggar Tari Kertha Jaya kept using the lexicons in Gambuh Dance Drama in order to maintain the language, especially Gambuh Dance Drama itself.